TESTES INICIAIS DA GERMINAÇÃO DE ESPÉCIES DE Myrsine Umbellata E Myrsine Coriacea - Conti, Daniela D.; Franco, Elcí T. H.; Marques, Claudia V.; Cidade, Márcia P. N. (Salão do Conhecimento, 2013)
Resumo